Vander's human physiology : The mechanisms of body function - Eric P. Widmaier, Hershel Raff, Kevin T. Strang (McGraw-Hill., 2006)
The fundamental purpose of this textbook is to present the principles and facts of human physiology in a format that is suitable for undergraduates regardless of academic background or field of study. This tenth edition features a clinically oriented focus to the study of human body systems